Comprehensive Review on the Role of Salivary Biomarkers and Prevention of Early Childhood Caries Using Herbal and Non-Herbal Products - Umapathy Thimmegowda; Pallavi Nagappa Kuri (Research Perspectives of Microbiology and Biotechnology Vol. 4, 2024)
Dental caries is a highly prevalent microbial chronic dental disease that affects a greater portion of the world’s population. Saliva surrounding the oral cavity’s soft and hard tissues contains both organic and inorganic components, some of which are important contributors to the host’s caries development, Saliva has shown great promise as a diagnostic fluid because, unlike blood or other bodily fluids, it contains a large number of diseases indicators. Saliva contains most of the enzymes that aid in metabolism. There are important enzymes associated with cell injury and cell death like salivary enzymes which play an important role in caries demineralization and remineralization. This review highlights the salivary alpha-amylase, alkaline phosphatase, and protease enzyme actions in early childhood caries and prevention.